The Influence of Profitability, Solvency and Company Size to Audit Report Lag - Banowaty Ayu; Bunga Indah Bayunitri (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2020)
The purpose of this study was to determine the effect of profitability, solvency, and company size on audit report lag. This research was motivated by a case of delayed reporting of financial statements to companies listed on the Indonesia Stock Exchange that has an impact on the decline in investor confidence in the company. The research method used the explanatory method. The independent variables in this study are profitability, solvency, and company size, while the dependent variable is the audit report lag. The data used secondary data, obtained through the company's annual financial statement data as research objects. The sample in this study were 10 companies from the population, as many as 50 companies. Hypothesis testing is done by multiple linear regression analysis using the IBM SPSS Statistics 20 program. The results showed that the profitability, solvency, and size of the company affect the audit report lag.